Management of Brain Metastases in Epidermal Growth Factor Receptor Mutant Non-Small-Cell Lung Cancer - Kelly, William J.; Shah, Neil J.; Subramaniam, Deepa S. (Frontiers in Oncology, 2018)
Lung cancer remains a leading cause of mortality with 1.69 million deaths worldwide. Activating mutations in Epidermal Growth Factor Receptor (EGFR), predominantly exon 19 deletions and exon 21 L858R mutations, are known oncogenic drivers identified in 20-40% of non-small-cell lung cancers (NSCLC). 39% of EGFR-mutant NSCLC patients develop brain metastases, compared to 28% in EGFR wild-type patients. First generation tyrosine kinase inhibitors (TKIs), such as erlotinib and gefitinib have proven to be superior to chemotherapy in the front line treatment of EGFR-mutant NSCLC, as has afatinib, a second generation TKI. The most common acquired resistance mechanism is the development of a gatekeeper mutation in Exon 20 T790M. Osimertinib has emerged as a third generation EGFR TKI with proven activity in the front line setting as well as in patients with a T790M acquired resistance mutation with remarkable CNS activity. As long term survival outcomes in EGFR-mutant NSCLC continue to improve, the burden of brain metastases becomes a greater challenge. Here we review the literature related to the management of brain metastases in EGFR-mutant NSCLC including the role of the three generations of EGFR TKIs, immunotherapy and brain radiation.